Third Plan Progress Report 1963-65, Planning Commission, Government of India - Planning Commission (Planning Commission, 1963)
The Indian economy was under considerable strain during the two years under review. The imbalances generated in the economy were reflected in the rising trend in prices, the difficulties met in raising sufficient resources for investment and the marked decline in foreign exchange reserves. The primary factor on the supply side underlying the difficult economic situation was the stagnation in agricultural output during the first three years of the Third Plan (1961—64). In 1963-64 there was a slight increase in the agricultural output but the production of foodgrains was below the level achieved two years earlier in 1961-62.
Planning Commission, Government of India